The past meets the present: exploring the biogeography of extant plecoptera of South Africa with reference to ancient middle permian fossil forms from the Onder Karoo locality near Sutherland - Kirkaldy, Benjamin Puleng (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
The Onder Karoo fossil locality near Sutherland, Northern Cape, recently yielded an unprecedented diversity of middle Permian insects, which were preserved in deposits of an aquatic lake margin system, in the Lowermost Abrahamskraal Formation. A large number of Plecoptera (stonefly) specimens were found, and this study represents an in-depth analysis of these species in the context of plecopteran evolution. A significant contribution to current knowledge of the Plecoptera from the middle Permian to the present has been made, utilizing a combination of fossil and phylogenetic evidence to better understand the origins, evolution, diversity and biogeography of the stoneflies. Three new plecopteran species have been described from the Onder Karoo locality, which is recognized here as the first Lagerstätte of its kind in Gondwana. Possible ecological links and relationships with the plecopterans described here have been suggested, using extant Plecoptera as analogues. An in-depth, fossilcalibrated, dated phylogeny of the Plecoptera was completed, using representatives from all three dominant lineages, the Antarctoperlaria, Systellognatha and the Euholognatha. This provides strong support for the monophyly of the Notonemouridae and the Antarctoperlaria, however the monophyly of Systellognatha and Euholognatha was not supported. The Notonemouridae were found to represent an earlier divergence than previously believed, forming a sister group to the remaining Plecoptera. Through a combination of fossil and molecular evidence, strong support was found for the current distribution of the Plecoptera worldwide being attributable to vicariance caused by the rifting of Pangea, and subsequently Gondwana and Laurasia, and long range dispersal. The focussed effort to include Southern Hemisphere stoneflies throughout this study has been a valuable step in reducing the Northern Hemisphere bias which currently dominates plecopteran research and has assisted in opening the way for future research into this important group on a global scale.
Keywords: Stoneflies, Fossil -- South Africa -- Northern Cape; Palaeopteron -- South Africa -- Northern Cape; Stoneflies -- Evolution; Insects, Fossil -- South Africa -- Northern Cape; Paleoentomology; Paleoentomology -- South Africa -- Northern Cape